Correlation between De Ritis Ratio with Severity of Covid-19 Patients Severity - Rostini, Tiene; Khairunnissa, Khairunnissa; Turbawaty, Dewi Kartika (Fakultas Kedokteran Universitas Brawijaya, 2024)
SARS COV-2 is the causative agent of the infectious disease Corona Virus Illness-19 (Covid-19). Covid-19 can cause damage to multiple organs, including the liver. The de Ritis ratio is a ratio between AST and ALT in blood serum, which may be a useful indicator for assessing liver damage in Covid-19 patients. The aim of this study is to determine the association between the severity of liver injury and an increase in the de Ritis ratio in Covid-19. The study population included patients with acute Covid-19 disease whose infection was validated using real-time PCR. A retrospective cross-sectional study was conducted. There were 1.983 subjects included, and 1.123 belonged to the moderate, 673 severe, and 181 to the critical groups. Calculations using Spearman rank revealed a strong significant association between De Ritis ratio and Covid-19 grade severity (rs=0.624, p<0.001). The more severe Covid-19, the higher de Ritis ratio values. The ROC curve of de Ritis ratio with Covid-19 severity shows AUC of 0.771 (P<0.001), sensitivity of 63.5%, specificity of 90.6%, PPV of 98.5% and an NPV of 20.02%. In conclusion, the severity of Covid-19 symptoms increases proportionally with the de Ritis ratio.